Effect of Iron Fertilization on Growth, Yield and Economics of Groundnut (Arachis hypogaea L.) - Poonia, Tanuja; Bhunia, S. R.; Choudhary, Rakesh (International Journal of Economic Plants, 2022)
A field experiment was conducted to study the effect of iron fertilization on growth, yield and quality of groundnut (Arachis hypogaea L.) during kharif, 2016 (June to September at instructional farm, Swami Keshwanand Rajasthan Agricultural University, Bikaner, Rajasthan, India. Twelve iron fertilization treatments viz. T1: control (water spray); T2: FeSO4 basal @ 25 kg ha-1; T3: Foliar spray of citric acid @ 0.1% at 45 and 75 days after sowing (DAS); T4: Foliar spray of FeSO4 @ 0.5% at 45 and 75 DAS; T5-T2+5 ton FYM ha-1; T6- T2+foliar spray of FeSO4 @ 0.5% at 45 and 75 DAS; T7: T3+T4; T8: T2+T3+5 ton FYM ha-1; T9: T2+T3+T4; T10: T3+T4+5 ton FYM ha-1; T11: T2+T4+5 t FYM ha-1; T12: T2+T3+T4+5 t FYM ha-1 were tried in randomized block design with three replications. Application of FeSO4 @ 25 kg ha-1 as basal+Foliar spray of FeSO4 @ 0.5% at 45 and 75 DAS+Citric acid @ 0.1% at 45 and 75 DAS+5 t FYM ha-1 (T12) found the best treatment combination with respect to pod yield, haulm yield and biological yield as compared to other treatment combinations. Treatment T12 improved the kernel yield by 37.2 and 18.2%, and straw (haulm) yield by 22.6 and 14.9% as compared to T1 and T2, respectively. Similarly, T12 recorded the ~49 and 20% higher net returns and ~20% higher B:C ratio as compared to T1 and 17 and 2% as compared to T2. The study showed that application of FeSO4 both as basal and foliar spray along with citric acid and FYM application gives the best results in dry ecologies of western Rajasthan.